2006
DOI: 10.1002/job.373
|View full text |Cite
|
Sign up to set email alerts
|

Psychological capital development: toward a micro‐intervention

Abstract: SummaryAfter first providing the meaning of psychological capital (PsyCap), we present a micro-intervention to develop it. Drawn from hope, optimism, efficacy, and resiliency development, this PsyCap Intervention (PCI) is shown to have preliminary support for not only increasing participants' PsyCap, but also financial impact and high return on investment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
986
2
63

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,093 publications
(1,079 citation statements)
references
References 8 publications
28
986
2
63
Order By: Relevance
“…It is therefore likely that mastering career competencies would lead to an enhanced evaluation of one's ability to control and impact upon one's work and career. In line with this reasoning, Akkermans et al (2013) found a positive relationship between career competencies and self-efficacy, a concept generally considered to be a personal resource (e.g., Avey, Luthans, & Jensen, 2009;Luthans, Avey, Avolio, Norman, & Combs, 2006). Finally, Xanthopoulou, Bakker, Demerouti, and Schaufeli (2007) noted that personal resources are, to some extent, malleable and open to development.…”
Section: Career Competencies and Personal Resourcesmentioning
confidence: 95%
See 1 more Smart Citation
“…It is therefore likely that mastering career competencies would lead to an enhanced evaluation of one's ability to control and impact upon one's work and career. In line with this reasoning, Akkermans et al (2013) found a positive relationship between career competencies and self-efficacy, a concept generally considered to be a personal resource (e.g., Avey, Luthans, & Jensen, 2009;Luthans, Avey, Avolio, Norman, & Combs, 2006). Finally, Xanthopoulou, Bakker, Demerouti, and Schaufeli (2007) noted that personal resources are, to some extent, malleable and open to development.…”
Section: Career Competencies and Personal Resourcesmentioning
confidence: 95%
“…Previous studies have shown that personal resources may act as a mediator in the motivational process (e.g., Llorens, Schaufeli, Bakker, & Salanova, 2007;Luthans et al, 2006;Xanthopoulou et al, 2007). That is, job resources can activate personal resources, which can subsequently lead to higher levels of work engagement.…”
Section: The Current Studymentioning
confidence: 99%
“…Just as the positive resource of psychological capital development has been recently demonstrated (see Luthans, Avey, Avolio, Norman, & Combs, 2006;Luthans et al, 2007), the identified components of the positive form of psychological ownership (i.e., self-efficacy, accountability, sense of belongingness, and self-identity) may also be developed in carefully designed and executed training interventions. Moreover, based on the relationship that transformational leadership seems to have on psychological ownership, the recent work on leadership development in general, and authentic leadership development in particular (e.g., see Gardner, Avolio, Luthans, May, & Walumbwa, 2005), would seem to have significant practical implications for psychological ownership management and development, and, in turn, performance impact in organizations.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Similarly, Luthans et al (2006) suggested that training boosting job resources (e.g., goal setting, goal clarification or quality feedback) may increase employees' "psychological capital," whose central dimension is self-efficacy. There is preliminary support that such interventions may bring financial profit and high return on investment (Luthans et al, 2006).…”
Section: The Mediating Role Of Self-efficacymentioning
confidence: 99%